Short Communication: Land cover changes from 2005 to 2015 in Mantangai area of Dayak Ngaju, Central Kalimantan, Indonesia - Bambang Hero Saharjo; Erekso Hadiwijoyo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saharjo BH, Hadiwijoyo E. 2019. Short Communication: Land cover changes from 2005 to 2015 in Mantangai area of Dayak Ngaju, Central Kalimantan, Indonesia. Biodiversitas 20: 2596-2602. Forest and land fires in Indonesia are well recognized, directly or indirectly, as the main contributors to deforestation and greenhouse gas emission related to the global climate change. Usually, local peoples are blamed for those fires especially when negative impact occurred. Fortunately, not all of the local peoples do the same thing as it is shown by Dayak Ngaju in Block A of ex-Mega Rice Project (Ex-MRP) Project area located in Mantangai sub-district Kapuas district, Central Kalimantan Province, Indonesia, where this research was conducted. The objective of this study was to know land the cover changes related to the use of fire for land preparation, and how the Dayak Ngaju people implement their knowledge and experience in the field. This objective was achieved by analyzing satellite images of Landsat 7 and 8 for a period of time starting from 2005 to 2015. Results of the research showed that the local people started clearing the land with fire at the end of September (dry season) or early October (the rainy season) yearly, as it could be seen from the changes of the land cover from secondary swamp forest into swamp shrub and from secondary swamp forest into fields. Meanwhile, at the protected area where peat was dominant, land cover change occurred due to land rights conflicts, and not to the use of fire for land preparation using fire by Dayak Ngaju communities, because they found that the results were not good and the planted rice would die three months after planting..